Assessing business structure: a case study in the energy industry - McDonald, Michael (Henry Stewart Talks, 2015)
Overview of the offshore drilling industry, Growth vs. value oriented firms, Master limited partnership, Spinoff vs. MLP comparison, Hypothetical firm profile